Surveillance of Mosquitoes (Diptera, Culicidae) in a Northern Central Region of Spain: Implications for the Medical Community - Ruiz-Arrondo, Ignacio; McMahon, Barry J.; Hernández-Triana, Luis M.; Santibañez, Paula; Portillo, Aránzazu; Oteo, José Antonio (Frontiers in Veterinary Science, 2019)
Mosquitoes are important to public and animal health due to their capacity to transmit diseases. Since the Zika Virus was declared a pandemic by the WHO in 2016, and it has been recorded in different regions of Mediterranean Area (included Spain), the Government of La Rioja (Northern Spain), through the Center of Rickettsiosis and Arthropod-Borne Diseases, implemented an entomological surveillance programme of mosquitoes in La Rioja and in a close area of Navarra. This surveillance extended to some of the pathogens that they can transmit. Here we describe the framework of the initial surveillance programme for the detection of mosquitoes and associated human pathogens. We outline the benefits and the limitation of the programme to date, and explore how greater benefits can be achieved, for example using a One Health approach. Entomological surveillance has been carried out with BG-Sentinel traps, human bait technique and other methods such as collecting adults in resting places or immature stages by dipping in several wetlands. Since Aedes albopictus, vector of arbovirus such as Dengue, Chikungunya and Zika, is absent in the region, the entomological programme included the surveillance of this exotic species using ovitraps in the most important cities. Morphological identification was supported using the mitochondrial cytochrome C oxidase subunit I and the internal transcribed spacer 2 genes analysis. In 2016 and 2017, more than 6,000 mosquitoes were collected. The mosquito’s community included 21 species associated with six genera: Anopheles (n=4), Aedes (n=5), Culex (n=6), Culiseta (n=4), Uranotaenia (n=1) and Coquillettidia (n=1). Eleven species represent new records for La Rioja and Navarra regions. Several species were collected biting humans and a great proportion of the sampled mosquito population are competent vectors of several pathogens, such as West Nile virus. Flavivirus detection in the target mosquito species is on-going, although results to date have been negative. At the same time, the epidemiological surveillance emphasis is placed in the early detection of mosquito-borne diseases in primary health and emergency services. The surveillance programme represents a relevant and necessary assessment of the risk of pathogen transmission in a region, and it allows establishing the appropriate preventive measures.